A dynamic game model for assessing risk of coordinated physical-cyber attacks in an AC/DC hybrid transmission system - Liu, Xuecheng; Shi, Libao (Frontiers in Energy Research, 2023)
The widely used intelligent measuring equipment not only makes the operation of AC/DC hybrid transmission system more safe and reliable, but also inevitably brings new problems and challenges such as the threats and hidden dangers of cyber attacks. Given this, how to effectively and comprehensively assess the inherent vulnerabilities of AC/DC hybrid transmission systems under the coordinated physical-cyber attacks is of critical significance. In this paper, a three-stage physical-cyber attack and defense risk assessment framework based on dynamic game theory is proposed. In the framework, the dynamic game process between attacker and defender is carried out for the power grid risk, which is expressed as the product of the attacker’s success probability in attacking the substation and the load loss caused by the attack. Regarding the probability of a successful attack, it depends on the number of funds invested by both attacker and defender sides considering the marginal effect, while the corresponding load loss caused depends on the cyber attack vector and the optimal load shedding scheme. For the solution of the proposed three-stage dynamic game framework, it is converted into a bi-level mathematical programming problem, in which the upper-level problem is solved by using the backward induction method to get the subgame perfect Nash equilibrium, and the lower-level problem is solved by using an improved particle swarm optimization algorithm to get the optimal amount of load shedding. Finally, the case study is performed on a modified IEEE 14-node AC/DC hybrid transmission test system, and the inherent weaknesses of the power grid are identified based on the risk assessment results, verifying the effectiveness of the proposed framework and method.